2015
DOI: 10.1002/anie.201409694
|View full text |Cite
|
Sign up to set email alerts
|

Significant Enhancement in the Efficiency and Selectivity of Iron‐Catalyzed Oxidative Cross‐Coupling of Phenols by Fluoroalcohols

Abstract: Significant enhancement of both the rate and the chemoselectivity of iron-catalyzed oxidative coupling of phenols can be achieved in fluorinated solvents, such as 1,1,1,3,3,3-hexafluoropropan-2-ol (HFIP), 2,2,2-trifluoroethanol (TFE), and 1-phenyl-2,2,2-trifluoroethanol. The generality of this effect was examined for the cross-coupling of phenols with arenes and polycyclic aromatic hydrocarbons (PAHs) and of phenol with β-dicarbonyl compounds. The new conditions were utilized in the synthesis of 2'''-dehydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(75 citation statements)
references
References 60 publications
2
69
0
3
Order By: Relevance
“…Recently,P appo and co-workers made as ignificant contribution to this field by the discovery [46,63] that, depending on the solvent used during an oxidative coupling process,t wo different products (64 and 65)c an be obtained starting from 2,6-dimethoxyphenol (63;Scheme 9, top). In aHFIP solution, the initially formed radical [63ÀH]C is stabilized to ag reater extent than in DCE, thus it reacts with the most nucleophilic site of phenol 63 and leads to 64 through ar adical-anion coupling mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…Recently,P appo and co-workers made as ignificant contribution to this field by the discovery [46,63] that, depending on the solvent used during an oxidative coupling process,t wo different products (64 and 65)c an be obtained starting from 2,6-dimethoxyphenol (63;Scheme 9, top). In aHFIP solution, the initially formed radical [63ÀH]C is stabilized to ag reater extent than in DCE, thus it reacts with the most nucleophilic site of phenol 63 and leads to 64 through ar adical-anion coupling mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…[16] These mildly acidic and highly polar solvents are strong hydrogen-bond donors (HBD) [17] that pair with hydrogenbond acceptor (HBA) groups such as ethers, peroxides, and carbonyl compounds. [16d, 17b, 18] Often fluorinated alcohols interfere with the catalytic cycle and positively affect the kinetic profile of polar reactions, significantly improving their efficiency [18,19] and selectivity. [20] With the notion that fluorinated alcohols can act as solvent-assisted selectivity in oxidation processes, we studied the autoxidation of methylarene by using the NHPI/Co(OAc) 2 catalytic system in HFIP.…”
mentioning
confidence: 99%
“…Pappo's group reported the fluoroalcohols on the iron‐catalyzed oxidative coupling of phenols . In 2015, Nakamura et al .…”
Section: Direct C–h Transformation By Iron Catalysismentioning
confidence: 99%
“…Pappo's group reported the fluoroalcohols on the iron-catalyzed oxidative coupling of phenols. 80,81 In 2015, Nakamura et al 82 reported that alkenes and arenes possessing a bidentate directing group can be alkylated with a primary or secondary alkylzinc halide in the presence of an iron/diphosphine catalyst and a dichloroalkane oxidant. Acrylamides, including unsubstituted and monosubstituted ones, react stereoselectively.…”
Section: Reviewmentioning
confidence: 99%